Disposal of expired medicines in Jordan: Practices of community pharmacists - Rania Hamed; Deemah Hasan H. Hasan; Alaa Hammad; Ameerah Hasan Ibrahim (PLoS ONE, 2026)
The handling of expired medicines in community pharmacies in Jordan is a critical issue that warrants greater attention. It impacts the environment, public health, and society. However, no studies have investigated the practices of community pharmacists in Jordan regarding the disposal of expired medicines. Therefore, this study aimed to evaluate the current practices of community pharmacists in Amman, Jordan, regarding the disposal of expired medicines and to assess the measures currently implemented to reduce the number of disposed medicines. A cross-sectional study was conducted among community pharmacists in Amman, Jordan, over three months, from November 2023 to January 2024. A 10-minute questionnaire was distributed either in a paper-based format or via an online platform. Data were analyzed using IBM SPSS version 26. The Chi-square test was used to assess the association between participants’ demographics and their responses to the questions. Of the 353 community pharmacists surveyed, 70.2% (n = 248) were under 40 years old, and 63.5% (n = 224) were female. The majority of the participating community pharmacists reported disposing of solids (n = 227, 64.5%), liquids (n = 206, 58.7%), semisolids (n = 213, 60.7%), and controlled drugs classified as Class B (n = 266, 76.2%) and Class C (n = 253, 72.5%) by returning them to pharmaceutical distributors. However, 75.4% (n = 267) reported a lack of knowledge about the disposal methods used by distributors for expired medicines. Most community pharmacists (n = 191, 57.5%) reported that supplements, including vitamins, minerals, and probiotics, were the most frequently expired products. To reduce expired medicines, community pharmacists most frequently relied on medical representatives to collect near-expiry items (n = 136, 38.5%) or limited stock (n = 125, 35.4%). Most community pharmacists (n = 248, 70.3%) reported awareness of the harmful effects of improper disposal of expired medicines on the environment. The study also found that 195 out of 353 community pharmacists (55.1%) had not received any course on the disposal methods of expired medicines during their pharmacy education. The present study highlighted the critical need for community pharmacists to be knowledgeable about proper disposal methods of expired medicines and to raise awareness of the establishment of specialized centers for their disposal.